2000
DOI: 10.4049/jimmunol.164.5.2386
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Difference to the Suppressive Effect of Prostaglandin E2 Among Mouse Strains: A Possible Mechanism to Polarize Th2 Type Response in BALB/c Mice

Abstract: PGE2 has been shown to play a prominent role in regulating Th1 and Th2 type responses. We studied the role of PGE2 in IFN-γ production by Staphylococcus aureus Cowan I-stimulated spleen cells from several mouse strains such as BALB/c, C3H/HeN, and C57BL/6. When spleen cells were pretreated with indomethacin (cyclooxygenase (COX)-1 and COX-2 inhibitor) or NS-398 (COX-2-specific inhibitor), S. aureus Cowan I -induced IFN-γ production was increased more markedly in spleen cells from BALB/c mice than from C3H/HeN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
2
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 53 publications
6
82
2
3
Order By: Relevance
“…Our finding is not in agreement with studies using human macrophages or DC; when considering the effects of IL-10 on DC phenotype and function, one should keep in mind that mouse and human DC populations are obviously not the same. Our results could be related to the high sensitivity of that lineage to the suppressive effect of PGE 2 , as was reported by Kuroda et al (58). However, in the data published by Kuroda, the distinctions between lineages exist only in terms of sensitivity, but there were no differences in terms of general orientation of the effects of PGE 2 on the immune response among the different mice.…”
Section: Discussioncontrasting
confidence: 42%
“…Our finding is not in agreement with studies using human macrophages or DC; when considering the effects of IL-10 on DC phenotype and function, one should keep in mind that mouse and human DC populations are obviously not the same. Our results could be related to the high sensitivity of that lineage to the suppressive effect of PGE 2 , as was reported by Kuroda et al (58). However, in the data published by Kuroda, the distinctions between lineages exist only in terms of sensitivity, but there were no differences in terms of general orientation of the effects of PGE 2 on the immune response among the different mice.…”
Section: Discussioncontrasting
confidence: 42%
“…PGE 2 suppressed the activation of NK cells, lymphokine-activated killer cells and cytotoxic T cells by inhibiting IL-2 receptor expression on effector cell surfaces [8]. Recently, we also found that PGE 2 suppressed IFNg and IL-12 production by macrophages (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the EP 4 -induced cAMP increase and the resultant activation of cAMP-dependent kinase during initiation of IL-12 gene activation may have a crucial effect on the following gene expression of this cytokine. A number of reports have established that the cAMPdependent pathway inhibits IL-12 production at the transcriptional level, possibly by affecting cAMP response element (CRE) binding complexes (31)(32)(33). Thus, EP 4 gene expression is down-regulated upon stimulation with LPS, but this receptor appears to have a pivotal role in autocrine regulation of cytokine release, and EP 2 might contribute to extend the inhibitory effect of PGE 2 on a dayscale duration.…”
Section: During Macrophage Activationmentioning
confidence: 99%